Benefits in treatment of congenital clubfoot using the Ponseti method – less aggressive with more efficiency - Matuszewski, Łukasz; Okoński, Marek; Gil, Leszek; Ostrowski, Jerzy; Okoński, Piotr (Polish Journal of Public Health, 2013)
Introduction. Clubfoot is one of the most common problems in pediatric orthopaedics. The treatment of clubfoot is controversial and continues to be one of the biggest challenges in pediatric orthopaedics.Aim. The main objective of this paper is to present advantages and benefits in treatment of congenital clubfoot by Ponseti method.Material and methods. The paper is based on material taken from patients treated in Children’s Orthopaedic Clinic and Rehabilitation Department Medical University of Lublin between the years 2007-2011. A group of 58 pa-tients with 69 idiopathic clubfeet was followed prospectively while being managed with the Ponseti method.Results. During the analysis of our final results we presented the data after follow-up of all patients (median 26 months), together with a sub-analysis of patients according to Pirani’s scale. It assessed the severity of clubfoot deformity and the response for treatment. The scores for all patients before the treatment ranged from 4.5 to 6 points. After the treatment we accomplished a score of 0.5 to1.5 points in all 69 treated feet. We evaluated the results of treatment as good or very good for 92% of patients. As comparison we retrospectively analyzed 125 patients treated between 1990-2000 with various type of operations. Those procedures ranged from a percutaneous heelcord lengthening to a wide release of medial, posterior, and lateral structures, with or without transfer of the anterior tibial tendon.Conclusions. Our study supports the principles of Ponseti’s method, because in cases when these principles were strictly obeyed all patients accomplished satisfactory results and there have been no recurrences that are known to us. Therefore, we strongly recommend using this method to avoid more invasive surgery in future. Non-operative treatment of clubfoot provides a lower complication rate, less pain, and higher function as the patient ages than operative treatment. That kind of treatment has led us to far to better results than the former more aggressive procedures. We emphasize the fact that other operational techniques have not been such efficient so far. Former surgery methods were either more complicated or more invasive.